PENGARUH DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT WINSEN KENCANA PERKASA - Vinando, Ricky; Saputra, Asron (LPPM Universitas Putera Batam, 2021)
The purpose of this study was to see the effect of work influence and satisfaction on employee performance at PT Winsen Kencana Perkasa by using a saturated sample technique. All populations consist of 130 respondents. The measuring instrument used by the hands is 5 pieces using a Likert scale. The data analysis method used is multiple linear regression analysis. The test of data quality in the study used validity and reliability tests, the classical assumption test in the study used the normality test, multicollinearity test and heteroscedasticity test and the multiplier test used multiple linear regression analysis and analysis of the coefficient of determination (R2), while testing the hypothesis in this study using the t test and the F test with the help of statistical software spss 25. Based on the results of this study indicate that work discipline and job satisfaction have a positive and significant effect on employee performance from t count> t table and significant value. <0.05 and work discipline and job satisfaction together have a positive and significant effect on employee performance from the> f table and a significant value <0.05.